2018
DOI: 10.1002/acm2.12418
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of TomoEDGE dynamic jaw field widths

Abstract: Dynamic jaw delivery on the TomoTherapy H‐series platform, entitled TomoEDGE™, is an effective tool to decrease the patient dose along the superior and inferior edges of the treatment target. The aperture of the TomoTherapy jaws, that is, field width (FW), defines the longitudinal dose profile. A consistent FW dose profile is an important quantity for accurate and reproducible dose delivery in TomoTherapy. To date, no evaluation has been made of the accuracy and precision of the dose profiles produced by dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…A 2-year study of dynamic jaw performance showed that 1% FWHM tolerance may not be consistently met for small asymmetric field widths. 64 Since the commissioned asymmetric beam either shares an inferior or superior edge with the jaw setting of the 5.0 cm field width which is calibrated to within 1% of its FWHM, that is, 0.5 mm, a tolerance of 0.5 mm is more reasonable for the asymmetric field width accuracy. In addition, these asymmetric beams only apply to the inferior and superior target edges over a longitudinal region of one fixed beam width.…”
Section: Treatment Delivery With Dynamic Jawsmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2-year study of dynamic jaw performance showed that 1% FWHM tolerance may not be consistently met for small asymmetric field widths. 64 Since the commissioned asymmetric beam either shares an inferior or superior edge with the jaw setting of the 5.0 cm field width which is calibrated to within 1% of its FWHM, that is, 0.5 mm, a tolerance of 0.5 mm is more reasonable for the asymmetric field width accuracy. In addition, these asymmetric beams only apply to the inferior and superior target edges over a longitudinal region of one fixed beam width.…”
Section: Treatment Delivery With Dynamic Jawsmentioning
confidence: 99%
“…Longitudinal beam profile data is shown for an SSD = 85 cm at d max . Figures reprinted with permission from Urso et al 64 …”
Section: Treatment Delivery Qamentioning
confidence: 99%
See 1 more Smart Citation
“…5 Urso et al attempted to evaluate the performance in terms of accuracy and precision of the dynamic jaws by measuring all 10 commissioned beam profiles of TomoEDGE technology for a 2-year duration. 6 Step-Wedge Helical) were the most susceptible to beam energy fluctuation. 9 Until now, no published studies on the evaluation concerning the relationship between TomoEDGE dynamic jaws field width and the energy variations.…”
Section: Introductionmentioning
confidence: 99%
“…Urso et al. attempted to evaluate the performance in terms of accuracy and precision of the dynamic jaws by measuring all 10 commissioned beam profiles of TomoEDGE technology for a 2‐year duration 6 . Binny et al.…”
Section: Introductionmentioning
confidence: 99%